Exposure to school and classroom racial segregation in Charlotte-Mecklenburg high schools and students' college achievement - Jason Giersch; Martha Cecilia Bottia; Roslyn Arlin Mickelson; Elizabeth Stearns (Arizona State University, 2016)
In this study we investigate Charlotte Mecklenburg Schools (CMS) high school graduates' academic performance in the first year of college and test whether their exposure to racial segregation in high school at both the school and classroom levels affected their college freshman grade point averages. Utilizing administrative data from the Roots of STEM Success Project, we track the CMS class of 2004 from middle school through its first year of education in the University of North Carolina (UNC) system. Our findings show that segregation among schools and among classes within schools compromises college achievement for students of color while offering no significant benefits to white students' college achievement.